Quinoxaline derivatives as a promising scaffold for breast cancer treatment. (17th May 2022) - Ezz Eldin, Rogy R.; Al-Karmalawy, Ahmed A.; Alotaibi, Mohammad Hayal; Saleh, Marwa A.
Abstract : Different mechanisms of action for the quinoxaline moiety to fight breast cancer. Abstract : According to Global Cancer Statistics 2021, female breast cancer has exceeded lung cancer as the most frequently diagnosed cancer. As a result of this widespread breast cancer, it is necessary to discover new drug candidates that avoid the side effects of current ones. So, researchers have studied and researched many heterocyclic chemical structures that were found to have strong anti-breast cancer activity. Among these structures are N-heterocycles, benzodiazines, a sequence of bicyclic heterocycles in which benzene rings are fused with 6-membered heterocycles containing two nitrogens. The quinoxaline moiety is a well-known and promising scaffold with previously known anticancer properties. This study covers the published work on anti-breast cancer compounds based on previous reference documents from recent years. It also shows the properties of new compounds with attractive anti-breast cancer properties that could be seen to be safer and free of adverse reactions. The compounds discussed here are attractive and promising scaffolds for treating breast cancer.